Recent advances on catalytic asymmetric difunctionalization of 1, 3-dienes. Issue 4 (24th January 2018) - Xiong, Yang; Sun, Youwen; Zhang, Guozhu
Graphical abstract: Highlights: Metal-catalyzed asymmetric difunctionalization of conjugated dienes in a highly regioselective fashion are realized. Eight metal catalysts are introduced by the number of frequency. Exquisite choosing diene coupling partners and reaction conditions are crucial for the high efficiency. Abstract: 1, 3-Dienes and derivatives are either feedstock chemicals or easily available materials. Catalytic difunctionalization of 1, 3-diene is one of the most powerful methods for carboncarbon bond formation with rapid increase of the molecular complexity and synthetic value in an atom economic way. By choosing proper metals and chiral ligands, a variety of catalytic asymmetric difunctionalization of conjugated dienes in a highly regioselective fashion have been reported. In this digest review, we will summarize recent advances on this topic based on different metals. We will also introduce unique phenomena that include reversal of regio- and diastereoselectivity.